Dadas as funções f: R → R definida por f (x) = 2x + 4 e g: R
+ R definida por
g (x) = 2x2 - 3x, determine f(g(5)).
Escolha uma opção:
a. 72
b. 70
c. 74
d. 0.78
Soluções para a tarefa
Respondido por
0
Resposta:
D
Explicação passo-a-passo:
Respondido por
2
Resposta: C
Explicação passo-a-passo:
f ( x ) = 2x + 4
g ( x ) = 2x² - 3x
f ( g ( x ) ) = 2 . g ( x ) + 4
f ( g ( x ) ) = 2 . ( 2x² - 3x ) + 4
f ( g ( x ) ) = 4x² - 6x + 4
f ( g ( 5 ) ) = 4 . ( 5 )² - 6 . ( 5 ) + 4
f ( g ( 5 ) ) = 4 . 25 - 30 + 4
f ( g ( x ) ) = 100 - 30 + 4
f ( g ( 5 ) ) = 74
Perguntas interessantes
Sociologia,
7 meses atrás
Matemática,
7 meses atrás
Sociologia,
9 meses atrás
História,
9 meses atrás
Matemática,
1 ano atrás